THE IMPACT OF SEAWEED BUSINESS MANAGEMENT ON INCOME ENHANCEMENT FOR THE MAMMINASAE GROUP IN BERARUE HAMLET, PANCANA VILLAGE, TANETE RILAU DISTRICT, BARRU REGENCY - Sri Hardianti Lukman; Rahmi Rais (Meraja journal, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal